Volatilitas Harga Daging Ayam Broiler di Tingkat Pedagang Pengecer pada Berbagai Kabupaten/Kota di Provinsi Jambi - Hasmon, Hafzi; Firmansyah, Firmansyah; Idris, Nahri; Hoesni, Fachroerrozi (Ekonomis: Journal of Economics and Business, 2024)
This research aims to analyze broiler chicken meat price volatility at the retail trader level in various districts/cities in Jambi Province. Forecasting analysis of broiler chicken meat prices in Jambi Province using time series secondary data in the form of daily data on the price of purebred chicken meat from 1 January 2023 to 31 October 2023 sourced from the National Food Agency. The analytical method used to determine volatility and the appropriate forecasting model for broiler chicken meat prices in Jambi Province uses the ARIMA, ARCH/GARCH model. The volatility of broiler chicken meat prices at the retail trader level in 11 districts/cities in the Jambi Province region varies, with the volatility in Kerinci District being the highest. The appropriate forecasting model for determining the price of broiler chicken meat in Jambi Province is the ARCH Model, which performs well in predicting the price of broiler chicken meat in Jambi Province.